Design and preliminary performance evaluation of a four wheeled vehicle with degraded adhesion conditions. (2017) - Pugi, Luca; Grasso, Francesco; Pratesi, Marco; Cipriani, Marco; Bartolomei, Argeo
Green shuttle vehicle (GSV) is a multi-purpose, four wheeled electric vehicle designed to operate in naturally protected areas where the conventional vehicles with internal combustion engines (ICEs) should be forbidden as a possible source of noise and pollution. The powertrain is based on a traction system with four in-wheel, permanent magnet motors that allow the vehicle to exhibit potentially interesting performances in terms of longitudinal dynamics, autonomy, and stability, even considering degraded adhesion conditions. In particular, this work also simulates the behaviour of the vehicle in degraded adhesion conditions, implementing a preliminary version of electric traction/braking fuzzy logic controller. The complete design and simulation of the system are an interesting example of how modern multi-disciplinary simulation tools can really accelerate the development of such a system with time and cost that are affordable also for small scale production series.